Workplace industrial relations in Britain, 1980 - 2004 - David G. Blanchflower; Alex Bryson; John Forth (Institute for the Study of Labor (IZA), 2006)
There was a time before the first Workplace Industrial Relations Survey (WIRS80) in 1980 when what we knew of industrial relations was based primarily upon small scale surveys and case studies. WIRS80 marked a radical departure in the study of industrial relations for two reasons. First, following in the footsteps of a small number of survey forerunners, it sought to 'map' industrial relations in Britain with nationally-representative large-scale surveys of workplace managers, thus permitting investigation of the incidence of practices and changes over time. Second, it focused on industrial relations institutions and outcomes, linking them to the processes of industrial relations that had been the chief focus of studies up until that point. This paper reflects on some of what we have learned in the five surveys over the quarter century since 1980, focusing selectively on the demise of collective IR, pay determination, union wage effects, variable pay, the climate of employment relations and union effects on employment growth.
urn:nbn:de:101:1-20080502121
Keywords: 330